The Transformational Impact of Learning to Teach Online - Carol A. McQuiggan (Adult Education Research Conference, 2009)
An action research study is being proposed in which professional development for faculty to prepare to teach online will be intentionally designed to promote transformational learning and inform classroom teaching practices by critically reflecting on and discussing their assumptions and beliefs about teaching.